COVID-19 Awareness of 140 Dental Assistants in Tehran, Iran: A Cross-Sectional Survey - M Sohrabi; S Alirezaie; Sh Amini (Islamic Azad University, 2021)
Background and Aim: The rapid outbreak of coronavirus disease 2019 (COVID-19) in Wuhan, China has led to a public health crisis. Dental professionals have a major role in preventing the viral infection cycle. This study targeted to investigate the knowledge of 140 dental assistants in Tehran, Iran, about COVID-19. Materials and Methods: A cross-sectional survey was conducted in Tehran, Iran, using a 27-item questionnaire, which consisted of 7 multiple-choice questions about the demographic information of the participants and 20 multiple-choice questions about their awareness. The data were analyzed with multivariable generalized estimating equations (GEE) using student t-test. Results: A total of 140 participants (22 males and 118 females with a mean age of 29.40±6.21 years) responded to the questionnaire. The majority of respondents (91.4%) mentioned cough and fever as the main symptoms of COVID-19 infection. Tooth extraction and root canal therapy were mentioned as emergency treatments according to 98.6% of respondents. 89.3% of respondents chose phone calls as the best screening tool. The knowledge and attitude of participants showed a significant correlation with their educational degree. Conclusion: The knowledge of dental assistants about COVID-19 infection was fair. The participants' awareness showed no correlation with their gender, work experience, place of occupation, and the specialty of the dentist that they assist.